Gambaran Tingkat Spiritualitas Anggota Paduan Suara Mahasiswa - Bestari, Dhiva Putri; Ulliya, Sarah; Sulisno, Madya; Dwidiyanti, Meidiana; Nurmalia, Devi (Holistic Nursing and Health Science, 2022)
Introduction: Singing particularly in a choir, has effects on long-life health, better nutrition, and a better perception of quality of life and health and has a role in the recovery and healing process. The spirituality of the choir is closely related to the connections among the members, teammates, coaches, and with God. The purpose of this study was to describe the spiritual level of members of the choir.Methods: This study was a descriptive quantitative type and designed using the “Daily Spiritual Experience Scale” (DSES) questionnaire to determine the level of spirituality which is then analyzed univariately. Thera ware 50 respondents joint in thia research.  The research was conducted online through the “g-form” and analysed using univariate analysis. Results: A total of 50 respondents participated and 9 respondents (18%) had moderate spirituality levels and 41 respondents (82%) had high spirituality levels.Conclusion: The results of this study can be concluded that most of the Choir have high spirituality levels